IMPROVEMENT IN SOYBEAN SPROUTS PRODUCTION WITH ULTRASOUND POWER - LOSADO, VAGNER ALEX MENDES; CANTELLI, KELI CRISTINA; STEFFENS, JULIANA; STEFFENS, CLARICE; CARRÃO-PANIZZI, MERCEDES CONCÓRDIA (Boletim do Centro de Pesquisa de Processamento de Alimentos, 2018)
The present work aimed the application of different ultrasound powers (10, 50 and 90W) to evaluate the germination and characteristics of soybean sprouts fromsoybeans of cultivar BRS 216 and 3 lines (A, B and C). In the germination test,the line A showed the highest percentage of germination (96% for 90W).The cultivar BRS 216 and line A present lower values of weight and higher yield of sprouts. The viable sprouts that presented the highest weight (for each 50g of soybean) were: line A followed by BRS 216, line C and B, with statistical differences (p<0.05) between them. For each 50g of soybean of cultivar BRS 216 and Lines A, B and C the production of viable sprouts was 231.47; 237.87; 170.74 and 199.94g, respectively, for 90W. In relation to the length of the sprouts using the power of 10W the line C presented a longer length. The line A using 90W showed better color characteristics. The highest protein value was found in cultivar BRS 216, for all applied potencies. With this work it can be concluded that the line A would be the most suitable for sprout production regardless of the ultrasound power applied